Revealing Photoluminescence Modulation from Layered Halide Perovskite Microcrystals upon Cyclic Compression. Issue 1 (4th November 2018) - Castelli, Andrea; Biffi, Giulia; Ceseracciu, Luca; Spirito, Davide; Prato, Mirko; Altamura, Davide; Giannini, Cinzia; Artyukhin, Sergey; Krahne, Roman; Manna, Liberato; Arciniegas, Milena P.
Abstract: Halide perovskites show promise for high‐efficiency solar energy conversion and light‐emitting diode devices owing to their bandgap, which falls within the visible optical range. However, due to their rigidity, GPa pressures are necessary to control the complex interplay between their electronic and crystallographic structure. Layered perovskites are likely to be controlled using much lower pressures by exploiting the optical anisotropy of the embedded organic molecules in the structure. This work introduces layered perovskite microplatelets and demonstrates the extreme sensitivity of their emission to cyclic mechanical loading in the range of tens of MPa. A drastic change in their emission is observed in situ, from near‐white to an enhanced blue color. This process is reversible, as is evident from a hysteresis loop in the photoluminescence (PL) intensity of the microplatelets. A combination of experimental analysis and computational modelling shows that such behavior cannot be attributed to changes in the crystallographic structure of the flakes. Instead, it suggests that, thanks to their structural anisotropy, microplate alignment and reorientation are responsible for the observed PL modulation. The possibility to tune the optical emission of layered perovskite crystals via low pressures makes them highly interesting as active materials in applications where stress sensing or light modulation is desired. Abstract : A significant enhancement of the blue emission is observed in low‐dimensional perovskite microplatelets by applying mild pressure in the range of MPa. This effect arises from pressure‐induced alignment of the platelets combined with the structural anisotropy of their optical properties, and not from uniaxial cell distortions that would require pressure in the range of GPa.